The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/nu11092024
|View full text |Cite
|
Sign up to set email alerts
|

Mice Lacking the Intestinal and Renal Neutral Amino Acid Transporter SLC6A19 Demonstrate the Relationship between Dietary Protein Intake and Amino Acid Malabsorption

Abstract: Dietary protein restriction has beneficial impacts on metabolic health. B0AT1 (SLC6A19) is the major transporter of neutral amino acids at the intestinal epithelia and absorbs the bulk of the diet-derived neutral amino acids from the intestinal lumen. It also reabsorbs neutral amino acids in the renal proximal tubules. Mice lacking B0AT1 show cellular outcomes of protein restriction, such as high FGF21 levels and low mTORC1 activity. Moreover, they have improved glucose homeostasis and resist diet-induced obes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 66 publications
2
27
0
Order By: Relevance
“…The association between intestinal flora and ACE2 has also been reported previously: deficiency of ACE2 caused critical impairment of local tryptophan homeostasis in a mouse model, which could alter the intestinal microbiome and susceptibility to inflammation (Hashimoto et al, 2012). ACE2 can also regulate the absorption of nutrients by binding with amino acid transporters on intestinal epithelial cells, which suggests that SARS-CoV-2 might compete with protein nutrients and interfere in their absorption through ACE2 on the intestinal epithelium (Singer et al, 2012;Vuille-Dit-Bille et al, 2015;Javed and Broer, 2019). Cole-Jeffrey et al indicated that the protective actions of ACE2 against cardiopulmonary disorders could be mediated by its actions on the gastrointestinal tract and intestinal flora (Cole-Jeffrey et al, 2015).…”
Section: Clinical Manifestations and The Possible Mechanism Of Intestsupporting
confidence: 63%
“…The association between intestinal flora and ACE2 has also been reported previously: deficiency of ACE2 caused critical impairment of local tryptophan homeostasis in a mouse model, which could alter the intestinal microbiome and susceptibility to inflammation (Hashimoto et al, 2012). ACE2 can also regulate the absorption of nutrients by binding with amino acid transporters on intestinal epithelial cells, which suggests that SARS-CoV-2 might compete with protein nutrients and interfere in their absorption through ACE2 on the intestinal epithelium (Singer et al, 2012;Vuille-Dit-Bille et al, 2015;Javed and Broer, 2019). Cole-Jeffrey et al indicated that the protective actions of ACE2 against cardiopulmonary disorders could be mediated by its actions on the gastrointestinal tract and intestinal flora (Cole-Jeffrey et al, 2015).…”
Section: Clinical Manifestations and The Possible Mechanism Of Intestsupporting
confidence: 63%
“…Preclinical studies have shown that dietary protein restriction can promote metabolic health [11,12,13,14,15,16]. In their paper, Javed and Bröer [17] show that mice lacking the neutral amino acid transporter B 0 AT1 have a serum amino acid profile resembling that of mice fed a low protein diet. Given that B 0 AT1 is the major transporter of neutral amino acids across the intestinal lumen and reabsorbs neutral amino acids in the renal proximal tubules [18], this reinforces that the inhibition of this transporter might be an attractive strategy to mimic the effects of dietary protein restriction to improve health and retard age-related disease [19].…”
mentioning
confidence: 99%
“…The phenotype of NOD global Slc6a19 knockout mice in this study had similarities and differences to C57Bl6J global Slc6a19 knockout mice [18,19]. Slc6a19 knockout induced marked aminoaciduria in mice of both backgrounds, but growth restriction, with reduced birth weight and subsequent weight gain, was seen only in C57Bl6J.Slc6a19 −/− mice [18].…”
Section: Discussionmentioning
confidence: 50%
“…Mutations in SLC6A19 cause Hartnup disorder, which is mostly a benign condition in adults, characterised by aminoaciduria [17]. Global Slc6a19 knockout on the C57BL/6J mouse caused marked aminoaciduria, reduced fed-state plasma amino acid levels, increased fibroblast growth factor 21 (FGF21), reduced glucose stimulated insulin secretion and improved glucose tolerance [18,19]. This suggests amino acid offloading through Slc6a19 deficiency reduces islet beta cell work, and consequently has the potential to reduce islet beta cell metabolic stress for prevention of both type 1 and type 2 diabetes [8,20].…”
Section: Introductionmentioning
confidence: 99%